Castillo, Gerardo. Local Experiences of Mining in Peru: Social and Spatial Transformations in the Andes. Nueva York: Routledge, 2020, 130 pp. (ISBN 978-0-367-25886-3) - Damonte Valencia, Gerardo (2020)
The book Local Experiences of Mining in Peru: Social and Spatial Transformations in the Andes shows us how experiences and representations are building and rebuilding mining sites. For this, the author incorporates us into the debates on the institutional, political, economic or cultural changes that contemporary corporate mining has promoted in Andean localities.